Redefining the Lexicon of Power, Envisioning the Future: The Atikamekw Nehirowisiw Nation and the Comprehensive Land Claims Negotiations - Éthier, Benoit; Ottawa, Gérald; Coocoo, Christian (Anthropologica, 2020)
<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Treaties and land claims negotiations between state institutions and Indigenous Peoples are necessarily tied to issues of territorial entanglements, resistance and coexistence. Regularly, studies of these negotiation dynamics make explicit the articulation and differentiation of Indigenous “life projects,” referring to the embodiment of socio-cultural desires, visions, aspirations and purposes – vis-à-vis neoliberal development projects. This article focuses precisely on the dynamics of negotiation in which the Atikamekw Nehirowisiwok (north-central Quebec) and state institutions have been involved for the last 40 years under the Comprehensive Land Claims Policy. More specifically, it addresses different policy mechanisms such as the extinguishment policy, burden of proof, debt obligations and results-based approach that are part and parcel of the negotiation process. Without disregarding the unequal power relations, this article also presents the motivations and aspirations expressed by the Atikamekw Nehirowisiwok in the negotiation process. It explains how their engagements are mobilised into <em style="box-sizing: border-box; color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">nehirowisiw orocowewin<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> – that is, a larger and deeper political and cultural project relating to the affirmation of <em style="box-sizing: border-box; color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">nehirowisiw miro pimatisiwin<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">, an Indigenous way of life and living well that is tied to the maintenance of a creative and open-ended coexistence based on reciprocity, complementarity, autonomy and consensus.